Enzymatic synthesis and phosphorolysis of 4(2)-thioxo- and 6(5)-azapyrimidine nucleosides by E. coli nucleoside phosphorylases - Stepchenko, Vladimir A.; Miroshnikov, Anatoly I.; Seela, Frank; Mikhailopulo, Igor A. (Beilstein Journal of Organic Chemistry, 2016)
The trans-2-deoxyribosylation of 4-thiouracil (4SUra) and 2-thiouracil (2SUra), as well as 6-azauracil, 6-azathymine and 6-aza-2-thiothymine was studied using dG and E. coli purine nucleoside phosphorylase (PNP) for the in situ generation of 2-deoxy-α-D-ribofuranose-1-phosphate (dRib-1P) followed by its coupling with the bases catalyzed by either E. coli thymidine (TP) or uridine (UP) phosphorylases. 4SUra revealed satisfactory substrate activity for UP and, unexpectedly, complete inertness for TP; no formation of 2’-deoxy-2-thiouridine (2SUd) was observed under analogous reaction conditions in the presence of UP and TP. On the contrary, 2SU, 2SUd, 4STd and 2STd are good substrates for both UP and TP; moreover, 2SU, 4STd and 2’-deoxy-5-azacytidine (Decitabine) are substrates for PNP and the phosphorolysis of the latter is reversible. Condensation of 2SUra and 5-azacytosine with dRib-1P (Ba salt) catalyzed by the accordant UP and PNP in Tris∙HCl buffer gave 2SUd and 2’-deoxy-5-azacytidine in 27% and 15% yields, respectively. 6-Azauracil and 6-azathymine showed good substrate properties for both TP and UP, whereas only TP recognizes 2-thio-6-azathymine as a substrate. 5-Phenyl and 5-tert-butyl derivatives of 6-azauracil and its 2-thioxo derivative were tested as substrates for UP and TP, and only 5-phenyl- and 5-tert-butyl-6-azauracils displayed very low substrate activity. The role of structural peculiarities and electronic properties in the substrate recognition by E. coli nucleoside phosphorylases is discussed.
Keywords: enzymatic glycosylation; PM3 and ab initio calculations; recombinant E. coli uridine, thymidine and purine nucleoside phosphorylases; substrate properties; 4(2)-thioxo- and 6(5)-aza-uacil and -thymine